2020
DOI: 10.1002/pon.5368
|View full text |Cite
|
Sign up to set email alerts
|

The development of a web‐based resource to provide information and psychosocial support to informal cancer carers in hospitals in Vietnam

Abstract: , H. (2020). The development of a webbased resource to provide information and psychosocial support to informal cancer carers in hospital in Vietnam. Psycho-oncology, 29(5), 920-926.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 17 publications
(26 reference statements)
0
32
1
Order By: Relevance
“…Our data demonstrate that slightly >50% of patients with DM possess adequate DM health literacy in Gansu Province, China, which is substantially lower compared with those patients with DM in the developed countries (90%) (31). The big difference between our current finding (50%) and others within the developed countries (90%) may be due to the timing of the establishment/development of internet infrastructure, which has been much early in the developed countries; whereas the development of the internet has occurred at least a decade later in Gansu, China (32). Moreover, Gansu Province has the lowest economic GDP in China, which would substantially impact business and education, and also internet infrastructure, compared with the highest GDP regions in China (e.g., Shanghai or Beijing) (33).…”
Section: Discussioncontrasting
confidence: 67%
“…Our data demonstrate that slightly >50% of patients with DM possess adequate DM health literacy in Gansu Province, China, which is substantially lower compared with those patients with DM in the developed countries (90%) (31). The big difference between our current finding (50%) and others within the developed countries (90%) may be due to the timing of the establishment/development of internet infrastructure, which has been much early in the developed countries; whereas the development of the internet has occurred at least a decade later in Gansu, China (32). Moreover, Gansu Province has the lowest economic GDP in China, which would substantially impact business and education, and also internet infrastructure, compared with the highest GDP regions in China (e.g., Shanghai or Beijing) (33).…”
Section: Discussioncontrasting
confidence: 67%
“… 10 17 A codesign process was used for conceptualising and implementing an online cancer carer resource in the UK 18 and Vietnam. 19 Common carer issues were elucidated with cancer carers and cancer-specific healthcare professionals (HCPs) to inform construction of the online interventions. This study will follow this methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Informal caregivers are of particular importance to the delivery of care for Vietnamese NCDs patients. First, caregivers undertake multiple caring roles for patients, helping access health care, making treatment decisions, providing informational and emotional support, and basic care needs (ie, daily care, nutrition) [ 2 , 5 ]. Second, due to the inter-dependence of patient and caregivers’ health, supporting caregivers has the potential to impact upon patients’ health and well-being.…”
Section: Reflectionsmentioning
confidence: 99%
“…Our recent study on cancer caregivers in Vietnam showed that the development of a web-based resource was identified as an urgent need. A web-based resource was viewed as a suitable interface to provide support across regions in a sustainable way [ 5 ]. The study demonstrates that for cancer, caregivers and health care professionals are supportive of a web-based intervention whilst recognising that this mode of delivery has limitations particularly in terms of accessibility for older caregivers and those that live in very remote locations.…”
Section: Reflectionsmentioning
confidence: 99%